Exploring the Use of Mobile Technologies in Indonesian Mathematics Lectures - Isnawan, Muhamad Galang; Alsulami, Naif Mastoor; Sudirman, Sudirman; Yanuarto, Wanda Nugroho; Sukarma, I Ketut (Kreano, Jurnal Matematika Kreatif-Inovatif, 2024)
Despite extensive research on mathematics within universities, yet exploration of alternative solutions for challenges students faced during mathematics lectures was limited. Particularly, integrating mobile technology assistance via didactical design research received little attention. Therefore, researchers tried to describe the role of mobile technology in supporting mathematics lectures at an Indonesian university. Didactic design research was the method used in this research. Participants comprised 53 students aged 18–25 years. The main research tools included the researcher, a math comprehension test, an in-depth interview guide, and a hybrid mathematics module with mobile technology support. Thematic analysis uncovered learning barriers, while lecture data underwent qualitative and retrospective analysis. The findings were low mastery of prerequisites, carelessness, and a limited context for lecture. The hybrid module was able to minimize mathematics student learning obstacles in higher education. This research recommends lecturers facilitate problem-based activities with mobile technology to enhance students competencies in higher education. Cukup banyak penelitian yang mengkaji matematika di universitas, tetapi eksplorasi mengenai solusi alternatif terhadap tantangan yang dihadapi mahasiswa selama kuliah matematika masih terbatas. Khususnya, pengintegrasian teknologi seluler melalui penelitian desain didaktis kurang mendapat perhatian. Oleh karena itu, penelitian ini mencoba untuk mendeskripsikan peran teknologi seluler dalam mendukung kuliah matematika pada sebuah universitas di Indonesia. Didactical design research merupakan metode yang digunakan dalam penelitian ini. Pertisipan terdiri dari 53 mahasiswa berusia 18–25 tahun. Instrumen utama adalah peneliti, tes pemahaman matematika, panduan wawancara mendalam, dan modul matematika hibrida dengan dukungan teknologi seluler. Analisis tematik digunakan untuk mengkaji hambatan belajar, sementara data perkuliahan dianalisis menggunakan kombinasi antara analisis kualitatif dan retrospektif. Temuan penelitian ini adalah penguasaan prasyarat yang rendah, kecerobohan, dan konteks perkuliahan yang terbatas. Modul hibrida mampu meminimalkan hambatan belajar mahasiswa matematika di pendidikan tinggi. Penelitian ini merekomendasikan kepada dosen untuk memfasilitasi kegiatan berbasis masalah dengan teknologi seluler untuk meningkatkan kompetensi mahasiswa di pendidikan tinggi.